Water footprint in industries: A systematic bibliographical survey from 2011 to 2016 - Pires, Luana Ferreira [UNESP]; Bernardo, Cristiane Hengler Corrêa [UNESP]; Satolo, Eduardo Guilherme [UNESP]; Queiróz, Timóteo Ramos [UNESP]; Morales, Angélica Gois [UNESP] (Centro Universitario de Maringa, 2018)
A systematic bibliographic survey was undertaken with regard to scientific publications on the application of Water Footprint within the industrial environment during the 2011-2016 period. Methodology consisted of the systematic bibliographic survey plot. Publications on the subject are still within an emergent and exploratory stage. Even though such studies are on the increase and several scientific journals are eager to publish results, the literature lacks a bibliography that deals with the use of the index, especially within the industry sector. This is due to a greater recurrence of the field approach. Several research works are possible.
Pegada hídrica no ambiente industrial: Uma revisão bibliográfica sistemática de 2011 a 2016
Keywords: Industry; Systematic bibliographic survey; Water